The Apostasy Penalty in Contemporary Islamic Jurisprudence: A Comparative Analysis and Contextual Interpretation - Mohamed Mahmoud El Gammal; Saepul Anwar; Hussein Bbaale (Universitas Islam Negeri Jakarta, 2026)
This study examines the evolving discourse on the punishment for apostasy (riddah) in Islamic jurisprudence by analyzing its classical foundations and contemporary relevance. Using a comparative approach, it examines the legal positions of the major Sunni schools and the Ẓāhirī tradition, while assessing responses from modern scholars and fatwa institutions to shifting political structures, social realities, and evolving concepts of citizenship. The research evaluates whether the classical death penalty for apostasy remains theologically justified and legally applicable in contemporary nation-states characterized by religious pluralism and individual rights. Through an examination of Quranic texts, prophetic traditions, historical precedents, and juristic methodologies, the study distinguishes apostasy associated with rebellion, treason, or public sedition from apostasy arising from private belief or personal conviction. The findings suggest that classical jurists frequently linked apostasy to threats against communal stability and political order rather than to disbelief alone. Accordingly, the study argues that contemporary interpretations should be guided by the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the preservation of life, intellect, religion, and human dignity. It concludes that modern applications of apostasy rulings require contextual evaluation and cautions against the political instrumentalization of religious law in contemporary societies. Abstrak Penelitian ini menganalisis perkembangan pandangan mengenai hukuman bagi pelaku murtad (riddah) dalam fikih dengan menelaah dasar-dasar pemikiran klasik serta relevansinya pada masa kini. Dengan menggunakan pendekatan komparatif, penelitian ini mengkaji pandangan mazhab-mazhab Sunni dan mazhab Ẓāhirī, serta menganalisis tanggapan para ulama dan lembaga fatwa kontemporer terhadap perubahan sistem politik, kondisi sosial, dan konsep kewarganegaraan modern. Penelitian ini bertujuan untuk menilai apakah hukuman mati bagi pelaku murtad yang dikenal dalam fikih klasik masih memiliki dasar teologis dan dapat diterapkan dalam negara modern yang menjunjung pluralisme agama dan hak-hak individu. Melalui analisis terhadap ayat-ayat Al-Qur’an, hadis Nabi, fakta sejarah, dan metode istinbaṭ hukum para ulama, penelitian ini membedakan antara kemurtadan yang disertai tindakan pemberontakan, pengkhianatan, atau ancaman terhadap ketertiban umum dengan kemurtadan yang hanya berkaitan dengan keyakinan pribadi. Hasil penelitian menunjukkan bahwa banyak ulama klasik menghubungkan kemurtadan dengan ancaman terhadap stabilitas masyarakat dan negara, bukan semata-mata perubahan agama seseorang. Oleh karena itu, penelitian ini menegaskan bahwa pemahaman hukum kemurtadan pada masa kini perlu mempertimbangkan tujuan-tujuan syariat (maqāṣid al-sharīʿah), terutama perlindungan terhadap jiwa, akal, agama, dan martabat manusia. Penelitian ini menyimpulkan bahwa penerapan hukum kemurtadan dalam konteks modern memerlukan kajian yang kontekstual dan tidak boleh digunakan sebagai alat kepentingan politik.